1995
DOI: 10.1007/bf00170622
|View full text |Cite
|
Sign up to set email alerts
|

The resistance of cellulases and xylanases to proteolytic inactivation

Abstract: The sensitivity of a range of cellulases and xylanases to proteolytic inactivation was investigated. The xylanases, all the Clostridium thermocellum cellulases and cellulase E from Pseudomonas fluorescens subsp. cellulosa exhibited no decrease in catalytic activity during a 3-h incubation with proteinases of the small intestine. Under these conditions, the control Escherichia coli enzymes analysed had half-lives of 4.3-13.5 min. The addition of substrate significantly decreased the sensitivity of proteinase-la… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
29
0
2

Year Published

1996
1996
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 75 publications
(34 citation statements)
references
References 17 publications
3
29
0
2
Order By: Relevance
“…Because the extracellular environment of microbial ecosystems displays high proteinase activity (3), resistance to proteolytic degradation exerts a strong selection pressure on the evolution of extracellular enzymes such as xylanases. This view is consistent with the observation that extracellular xylanases from both mesophilic and thermophilic hosts are resistant to proteinases (3,5), whereas intracellular forms of these enzymes are susceptible to proteolytic attack (1). It is interesting to note that only three amino acid substitutions generate an enzyme that is more thermostable than the wild type xylanase, and thus, the dependence on calcium for this phenotype can easily be selected out.…”
Section: Discussionsupporting
confidence: 84%
“…Because the extracellular environment of microbial ecosystems displays high proteinase activity (3), resistance to proteolytic degradation exerts a strong selection pressure on the evolution of extracellular enzymes such as xylanases. This view is consistent with the observation that extracellular xylanases from both mesophilic and thermophilic hosts are resistant to proteinases (3,5), whereas intracellular forms of these enzymes are susceptible to proteolytic attack (1). It is interesting to note that only three amino acid substitutions generate an enzyme that is more thermostable than the wild type xylanase, and thus, the dependence on calcium for this phenotype can easily be selected out.…”
Section: Discussionsupporting
confidence: 84%
“…In this respect, two possible explanations are worth mentioning. On one hand, the concept of stabilizing domains has emerged from studies of proteins such as xylanases (44), in which the increased stability of one domain promotes the stability of the whole molecule. It is therefore tempting to consider the heatlabile unit of PGK as a destabilizing domain, providing the required flexibility around the active site in order to increase the catalytic rate at low temperature.…”
Section: Resultsmentioning
confidence: 99%
“…The domains were initially called cellulose-binding domains, but subsequently were changed slightly to stand for carbohydrate-binding modules (CBMs), as several have now been shown to bind polysaccharides other than cellulose (Boraston et al 2004;Gilbert et al 2013). The CBMs were separated from the catalytic domain by the serine rich linker region identify by Wolff et al Crystallographic data later indicated these serine linker regions were glycosylated, which conferred protection from proteolysis (Fontes et al 1995). These CBMs were essential for effective hydrolysis of crystalline cellulose, as shown by biochemical experiments with the CelE (Cel5B, locus ID CJA_2983) enzyme.…”
Section: Cellulose Degradationmentioning
confidence: 94%